Suppression of mast cell activity contributes to the osteoprotective effect of an herbal formula containing Herba Epimedii, Fructus Ligustri Lucidi and Fructus Psoraleae. (31st October 2013) - Chan, Ben Chung Lap; Lee, Hoi Ying; Siu, Wing Sum; Yip, Kwok Ho; Ko, Chun Hay; Lau, Clara Bik San; Leung, Ping Chung; Lau, Hang Yung Alaster
Abstract Objectives Mast cells are believed to contribute to the pathogenesis of osteoporosis as their number is increased in osteoporotic bones. Herba Epimedii, Fructus Ligustri Lucidi and Fructus Psoraleae are three Chinese herbs traditionally for tonifying the 'kidney system' and a herbal formula (ELP) containing the respective herbs at the weight ratio of 5 : 4 : 1 was shown to prevent osteoporosis. This study evaluated if suppression of mast cell accumulation and activity contribute to the anti‐osteoporotic action of ELP. Methods The herbs were boiled under reflux to produce the aqueous extract that was further concentrated under reduced pressure and lyophilized. An in‐vivo rat osteoporosis model using hind limb unloading was employed for studying the accumulation of mast cells. The human mast cell line, LAD2, was employed to evaluate the mast cell modulating action of ELP. Key findings Mast cell number in the tibiae of hind limb unloaded rats increased significantly during the course of osteoporosis. ELP treatment (10 g/kg/day) prevented both osteoporosis and mast cell accumulation in these rats. Furthermore, ELP significantly inhibited histamine and tumour necrosis factor‐α release from LAD2 cells. Conclusion Mast cells contributed to hormone independent osteoporosis. The suppression of mast cell accumulation and activation may contribute to the anti‐osteoporotic action of ELP.